Predicting Capacity and Distribution of Healthcare Facilities in West Java - Arvin Akbar Gumilang (Journal of Economics and Business UBS, 2023)
Inequitable distribution of healthcare infrastructure is a barrier to universal access. This research analyzes gaps in primary care facilities across 627 districts in Indonesia's West Java Province. A data-driven approach identifies shortages and proposes an evidence-based strategic construction plan to improve equity. Demand was forecast using national standards of 1 clinics per 30,000 population. While some areas meet or exceed standards, severe shortages affect many districts. Gap analysis quantified deficiencies by subtracting existing clinics from projected demand for each district using simple linear extrapolation for each kota and kabupaten. Quantifying gaps at district level highlighted disparities not evident in provincial summaries. The gap analysis methodology substantiated widespread inequities by comparing granular demand modeling to current infrastructure. Findings demonstrate analytical techniques incorporating sub-regional data can identify hidden disparities and inform targeted policy. The technique provides a data-driven approach to inform healthcare planning and resource allocation, with applications for regional systems globally. In 2020, Average demand was 2 puskesmas, ranging up to 15. In total 363 districts fell below the minimum national standard for clinics per capita. Mapping visualized clusters of highly deprived regions. In 2020, with West Java's 47 million residents, total modeled demand is 1771 puskesmas and up to 1959 in 2032. Current healthcare quantity was collected through web scraping district websites, finding only 1016 existing puskesmas. This reveals a significant shortage, with over 55% of districts below the standard. Distribution inequity was evident, with puskesmas density spanning 0-10 across District. These findings clearly demonstrate a need for expanded investment in primary care infrastructure. To achieve more equitable access, a multi-year strategic construction plan was proposed targeting new clinic development in underserved districts. The plan stratified districts into priority tiers based on the severity of shortages. Construction will be phased over 3 stages, focusing first on districts with the highest deprivation to rapidly improve equity.